Pengembangan Media Pembelajaran 3D Berbasis Flipbook Pada Mata Pelajaran Aplikasi Perangkat Lunak dan Interior Gedung (APLIG) Kelas XI DPIB di SMKN 2 Surabaya - Mochammad Alfian Supriono; Purwo Mahardi (Jurnal Kajian Pendidikan Teknik Bangunan, 2025)
This study aims to develop flipbook based e-module learning media to improve students' understanding of sketchUp software material in APLIG subjects. The research method used is research and development (R&D) with the 4D development model (define, design, develop, & disseminate). The data analysis used is data on the results of the feasibility of flipbook-based e-modules, learning implementation, and student responses. The results of the feasibility of flipbook-based e-modules were validated by a lecturer and a learning subject teacher by obtaining an average percentage of 84% material and 95% media, so it was categorized as very good (very feasible). The results of the implementation of learning using flipbook based emodules in class XI DPIB SMKN 2 Surabaya obtained an average percentage of 82% so that it could be categorized as very good (very feasible). The results of students' responses to the flipbook-based emodule learning media on SketchUp software material obtained a percentage of 78% so that it could be categorized as very feasible. It can be concluded that the learning in this research is very good.